2017
DOI: 10.5935/1414-8145.20170042
|View full text |Cite
|
Sign up to set email alerts
|

Family centered care in emergency departments: perception of brazilian nurses and doctors

Abstract: Cuidado centrado na família em unidades emergenciais: percepção de enfermeiros e médicos brasileirosCuidado centrado en la familia en unidades de urgencias: percepción de enfermeros y médicos brasileños Mayckel AbstrActObjective: To know the perception of doctors and nurses working in Emergency Care Units (ECU, in Brazil known as "UPA") on Family Centered Care (FCC). Methods: Descriptive study with qualitative approach conducted in two emergency units in Southern Brazil. Participated 32 health professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
2
7
0
3
Order By: Relevance
“…The 30 participants were equally divided between patients and family members. Eight patients were female; nine were between 19 and 59 years old and the other six were between 60 and 77 years old; nine had an employment relationship; eight had up to four years of study; and nine, low family income -up to a minimum wage per capita 1 . The reasons that triggered the search for the service involved neurological, cardiac, respiratory and automobile accidents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 30 participants were equally divided between patients and family members. Eight patients were female; nine were between 19 and 59 years old and the other six were between 60 and 77 years old; nine had an employment relationship; eight had up to four years of study; and nine, low family income -up to a minimum wage per capita 1 . The reasons that triggered the search for the service involved neurological, cardiac, respiratory and automobile accidents.…”
Section: Resultsmentioning
confidence: 99%
“…Family-centered care presupposes that patients' relatives are integrated into care and decision-making, including during hospitalization for acute and severe diseases (1) . Specifically, family presence during emergency care, defined as the permanence of one or more relatives in a place that allows visual and/or physical contact with the patient during the performance of procedures in Emergency Rooms and Intensive Care Units, is a recent and not yet fully established practice (2)(3) , but has over the years been increasingly endorsed by important international critical care organizations (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…By recognizing the importance of the family in the user's life, it can help modulate government health policies and programs; elaborate institutional projects, rules and routines; evaluate health care; and direct daily interaction between professionals, users and family members. 27 In this sense, mastery and a greater appropriation of communication and its elements would contribute to the family's cooperation to the service, as well as facilitate the relationship among the individuals involved in the care process.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out with Brazilian physicians and nurses concluded that professionals present difficulties in implementing this approach due to inadequate physical space, lack of preparation about the subject, absence of permanent education programs that address the issue, and the sociocultural profile of the population. Family centered care is still very incipient, it does not appear at various times involving the various levels of health care, much less is discussed in vocational training (7) .…”
Section: Introductionmentioning
confidence: 99%